Three new species of Docosia Winnertz from central and southern Europe (Diptera: Mycetophilidae) - Kurina, Olavi; Ševčík, Jan (Zootaxa, 2011)
Three new European species of Docosia Winnertz are described, photographed and their terminalia illustrated. Docosia muranica sp. nov. is described on the basis of material from central Slovakia and northern Greece, while the material of D. rameli sp. nov. and D. kerkini sp. nov. originates from northern Greece only. The number of described European species of Docosia has thus increased to 32.